2019
DOI: 10.4103/idoj.idoj_435_18
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic features of lower lip squamous cell carcinoma: A descriptive study

Abstract: Aim:Dermoscopic features of cutaneous squamous cell carcinoma (SCC) have been well described; however, there are a few studies focused on the dermoscopic aspect of lip SCC. In this study, we aimed to identify dermoscopic findings of lower lip SCC.Materials and Methods:The clinical and histopathologic features, dermoscopic images, and demographic data of the patients with histologically approved lip SCC were retrospectively evaluated.Results:A total of 10 lesions were enrolled in the study. Milky red structurel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
(22 reference statements)
1
11
4
Order By: Relevance
“…Vascular findings observed in our analysis are different from that described in the largest dermoscopic study on lip SCC to date by Benati et al involving 22 patients, in which polymorphous pattern was stated as the most common (68%), followed by linear‐irregular and dotted in 27.0% and 5.0% of cases, respectively 6 . Elmas et al reported “polymorphous vascular pattern” in 6/10 (60%) of their cases 7 . This named pattern was also reported in the anecdotal reports of lip SCC by Güleç and Peralta et al 8,9 However, the concept or the frequency of the so‐called “polymorphous pattern” can neither be compared between our study with others nor among these studies themselves.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Vascular findings observed in our analysis are different from that described in the largest dermoscopic study on lip SCC to date by Benati et al involving 22 patients, in which polymorphous pattern was stated as the most common (68%), followed by linear‐irregular and dotted in 27.0% and 5.0% of cases, respectively 6 . Elmas et al reported “polymorphous vascular pattern” in 6/10 (60%) of their cases 7 . This named pattern was also reported in the anecdotal reports of lip SCC by Güleç and Peralta et al 8,9 However, the concept or the frequency of the so‐called “polymorphous pattern” can neither be compared between our study with others nor among these studies themselves.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the “white‐colored structures,” we observed the presence of WSA, white halos, and white dots/globules, each feature in approximately one‐third (31‐36%) of the patients, with the majority observed in well‐differentiated followed by moderately‐differentiated histological variants. Note the relatively higher incidence of some of these white‐colored features reported by Benati et al and Elmas et al 6,7 with striking contrast with a lower frequency (comparable to our study) reported by Lallas et al in their 143 cases of cSCC. 5…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations